Model Pelayanan “Pengerja Gereja” Untuk Mewujudkan Pertumbuhan Gereja - Eunike Agoestina (Kaluteros Jurnal Teologi Dan Pendidikan Agama Kristen, 2019)
hurch Workers are believers who have been chosen, appointed, and appointed by the Church to help the ministry in the Church so that the Church experiences maximum growth. This responsibility is borne by church workers to realize the growth of the Church both in quantity and quality. The growth of the Church is for God and the work of God in His church, through the Holy Spirit which gives the growth of faith in the life of the congregation, which in turn affects the number of new souls in the church. The model of Church worker service that can be applied is through lay development services, service through cell groups, and personal service. Abstrak Indonesia Pengerja Gereja adalah orang percaya yang telah dipilih, ditetapkan, dan diangkat oleh Gereja untuk membantu pelayanan di Gereja agar Gereja mengalami pertumbuhan yang maksimal.Tanggungjawab ini diemban oleh pengerja gereja untuk mewujudkan pertumbuhan Gereja baik secara kuantitas maupun kualitas. Pertumbuhan Gereja adalah bagi Allah dan karya Allah dalam gerejaNya, melalui Roh Kudus yang memberikan pertumbuhan iman dalam kehidupan jemaat, yang pada akhirnya berdampak kepada pertambahan jumlah jiwa-jiwa baru dalam gereja. Model pelayanan pengerja Gereja yang dapat diterapkan adalah melalui pelayanan pengembangan kaum Awam, pelayanan melalui kelompok sel, dan pelayanan pribadi.